The effect of lithology and microstructure on the deformation of unstable rock slopes in northern Norway - Aamodt, Emilie Jensen (UiT Norges arktiske universitet, 2022)
Rock avalanches are a type of natural catastrophe in Norway with very high consequences, and the alpine landscape makes Troms and Finnmark County the region with the highest frequency of unstable rock slopes. The bedrock geology is highly relevant to assess and understand the failure mechanisms, and mechanical properties that influence deformation in rock slopes. Pre-existing structures and lithological changes may have the potential to affect the mechanical properties in unstable rock slopes. The meta-igneous bedrock at the unstable rock slope Dusnjarga in Kvænangen municipality and the meta-sedimentary bedrock at the high-risk object Gámanjunni 3 in Kåfjord municipality, are both located in Troms and Finnmark county, northern Norway. Failure of Dusnjarga and Gámanjunni 3 can cause catastrophic consequences with possible harm to life and infrastructure. Both Dusnjarga and Gámanjunni 3 have a high frequency of pre-existing large-scale discontinuities in the back scarp region and consistent brittle structures throughout the instabilities. Many of these discontinuities are recognized in microscopy, suggesting that small-scale structures affect the formation of large-scale discontinuities, and eventually, the presence of these structures can cause a point of rupture initiation on large instabilities. All investigated thin sections present consistent small-scale joint sets parallel and normal to foliation. Each rock type displays different structures and mineralogy, and the fracture behavior is not random. In addition, observed microfractures appear to propagate easier in a metamorphosed fabric and favor changes in texture. All small-scale observations can be linked to large-scale discontinuities in an unstable rock slope. Lithology has a strong control on the development and evolution of URS-related structures.